Product Market Competition And Analysts’ Forecasting Properties: Evidence From Korea - Lee, Jaehong; Mo, Kyoungwon (Journal of Applied Business Research, 2017)
In this paper, we examine the association between product market competition and financial analysts’ forecasting properties in a sample of 76,621 analyst-firm-year observations in South Korea between 2000 and 2014. Using the Herfindahl–Hirschman Index to proxy for product market competition, we document that financial analysts are likely to issue less accurate and more optimistic forecasts in highly competitive product markets. In addition, we find that analysts’ reports show more optimism in stock recommendations in firms with high market competition.